2013
DOI: 10.3390/ijms140611692
|View full text |Cite
|
Sign up to set email alerts
|

Wharton’s Jelly-Derived Mesenchymal Stem Cells: Phenotypic Characterization and Optimizing Their Therapeutic Potential for Clinical Applications

Abstract: Wharton’s jelly (WJ) is a gelatinous tissue within the umbilical cord that contains myofibroblast-like stromal cells. A unique cell population of WJ that has been suggested as displaying the stemness phenotype is the mesenchymal stromal cells (MSCs). Because MSCs’ stemness and immune properties appear to be more robustly expressed and functional which are more comparable with fetal than adult-derived MSCs, MSCs harvested from the “young” WJ are considered much more proliferative, immunosuppressive, and even th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
220
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(225 citation statements)
references
References 99 publications
4
220
0
1
Order By: Relevance
“…In the present study, liver from diabetic rats treated with camel Wharton's jelly mesenchymal stem cells showed improvement in the hepatic parenchyma and decrease the severity of lesions than liver of diabetic rats. These results agree with different studies suggested a supportive role of undifferentiated WJ-MSCs in rescuing injured liver functions [24]. In addition, WJ-MSCs have properties of anti-inflammatory and antifibrosis by endogenous secreted factors such as metalloproteinase [25].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, liver from diabetic rats treated with camel Wharton's jelly mesenchymal stem cells showed improvement in the hepatic parenchyma and decrease the severity of lesions than liver of diabetic rats. These results agree with different studies suggested a supportive role of undifferentiated WJ-MSCs in rescuing injured liver functions [24]. In addition, WJ-MSCs have properties of anti-inflammatory and antifibrosis by endogenous secreted factors such as metalloproteinase [25].…”
Section: Discussionsupporting
confidence: 92%
“…MSCs are obtained from several adult mesenchymal tissue sources such as: bone marrow [8], adipose tissue [9], synovial membrane [10], periosteum [11] and dental pulp [12] as well as from non-adult tissue sources such as the fetal tissue [13], amniotic fluid [14] umbilical cord tissue (Wharton's jelly) [15] and umbilical cord blood [16].…”
Section: Mesenchymal Stromal Cells Are Known To Differentiate Into a mentioning
confidence: 99%
“…After expansion, both hES-MSCs, Flb-MSCs were seeded in T75 culture flasks for RNA extraction and in 12-well plates for staining during differentiation of adipocytes, and osteocytes, and in pellet form in 15 …”
Section: Msc Differentiationmentioning
confidence: 99%
“…Research studies have reported that MSC has the capability to differentiate into osteoblasts, chondrocytes, cardiomyocytes, myocytes, adipose cells and even neural cells. MSC can be isolated from multiple areas in adult tissue such as bone marrow, adipose tissue, umbilical cords, and peripheral blood [2,3,4]. Umbilical Cord Derived Mesenchymal Stem Cells (UC-MSCs) have proliferation and differentiation capabilities.…”
Section: Introductionmentioning
confidence: 99%